The Alexandrian riots of 38 C.E. and the persecution of the Jews : a historical reconstruction - Gambetti, Sandra. (Supplements to the Journal for the Study of Judaism, 2009)
Scholars have read the Alexandrian riots of 38 CE according to intertwined dichotomies. The Alexandrian Jews fought to keep their citizenship - or to acquire it; they evaded the payment of the poll-tax - or prevented any attempts to impose it on them; they safeguarded their identity against the Greeks - or against the Egyptians. Avoiding that pattern and building on the historical reconstruction of the experience of the Alexandrian Jewish community under the Ptolemies, this work submits that the riots were the legal and political consequence of an imperial adjudication against the Jews. Most of the Jews lost their residence never to recover it again. The Roman emperor, the Roman prefect of Egypt and the Alexandrian citizenry - all shared responsibilities according to their respective and expected roles.